NINE-TEST PANEL HAS SUPERIOR SENSITIVITY TO DETECT ANTIPHOSPHOLIPID ANTIBODY SYNDROME IN PATIENTS WITH OR WITHOUT SLE - Dziamski, Konrad (Clin Immunol, 2020)
Anti-phospholipid antibodies (aPL) and lupus anticoagulant (LAC) represent diagnostic criteria for systemic lupus erythematosus (SLE) and underlie anti-phospholipid syndrome (APS) in patients with and without SLE. 526 healthy controls and 1633 SLE and 1835 primary APS (PAPS) patients were evaluated. LAC was assessed by hexagonal phase phospholipid neutralization assay (HPPNA), diluted Russell viper venom test (dRVVT), and platelet neutralization procedure (PNP). β2-glycoprotein-I and cardiolipin IgG, IgM, and IgA antibodies (aCL-IgG, aCL-IgM, aCL-IgA) were measured. 222/1633 SLE patients had APS based on the nine-test panel, which afforded the highest sensitivity (74%) and negative predictive value (90%) but lowest specificity (52%). HPPNA was the most sensitive individual test at 52%. The nine-test panel yielded the greatest sensitivity for aPL detection (70%) relative to HPPNA, the most sensitive individual test (36%) in PAPS. Superior sensitivity of a nine-test aPL panel has major implications for preventing potentially fatal thrombotic events in SLE and PAPS.